(NrADIOBIOLOGIQ ^ELOWEKA I VIWOTNYH (B:s (Nu^EBNOE POSOBIE (B/s - (NqRMONENKO(B, (NsAMUIL pETROWI^s ((NmOSKWA (B:s (NwYS[AQ [KOLA(B,s, 1977)
(NsPISOK LIT(B.: (NS(B. 352 - 355s
(NuKAZ(B. (NPREDM(B., (NIMEN(B.: (NS(B. 356 - 364s
Keywords: (NrADIOBIOLOGIQs